EMV mix design method for preparing sustainable self compacting recycled aggregate concrete subjected to chloride environment. (28th February 2019) - Rajhans, Puja; Gupta, Prashant Kumar; Kumar, Raju Ranjan; Panda, Sarat Kumar; Nayak, Sanket
Graphical abstract: Highlights: Self compacting recycled aggregate concrete (SCRAC) is being subjected to chloride environment. Equivalent mortar volume (EMV) method for chloride resistance SCRAC. Two stage mixing approach ( TSMAsfc ) for improving the chloride resistance. Justification of improvement of properties through microstructural investigation. Abstract: The present investigation is an effort to make sustainable self compacting recycled aggregate concrete (SCRAC) when the concrete is subjected to high probability of chloride ingress. Aproposed mix design method is employed in conjunction with Nan Su mix design method to study the chloride ions ingress of SCRAC. In this mix design method, the acceptable substitution of recycled concrete aggregate (RCA) depends on the residual mortar content (RMC) attached on the surface of RCA. The treatment on RCA is done by using a coat of sodium silicate along with silica fume to improve the properties of SCRAC mix. Finally, during mixing of ingredients different mixing approaches were followed to evaluate the chloride ion ingress depth, migration coefficient and microstructure of SCRAC. It is observed that SCRAC prepared with two stage mixing approach (TSMA sfc ) along with proposed method of mix design resulted improved compressive strength and chloride resistance properties. The reason of improvement of SCRAC by filling of pores and cracks in interfacial transition zone (ITZ) and adjacent to it is justified through microstructural investigation. Further, elemental mapping is also carried out to know the presence of different elements which contributes for improving the strength in concrete.